CHILDHOOD SEXUAL ABUSE AMONG UNDERGRADUATES OF EBONYI STATE UNIVERSITY, ABAKALIKI: PERSONALITY TRAIT, SUBSTANCE ABUSE AND LONELINESS AS PREDICTORS VARIABLES - Oginyi, C.N Ronald; Mbam, Ofoke Sunday; Nwonyi, Sampson; Nwankwo, Francisca; Oko, Felix Uchenna (EBSU Journal of Social Sciences and Humanities, 2024)
This study investigated childhood sexual abuse among undergraduates of Ebonyi State University, Abakaliki: personality trait, substance abuse and loneliness as predictors variables. A total of 228 participants comprising undergraduates were sampled from Ebonyi State University, Ababkaliki. Their ages ranged between 17 to 27 years with a mean of 21.54. The study adopted a cross sectional survey design. The instruments used for data collection included Personality trait inventory, substance abuse questionnaire, loneliness scale and childhood sexual abuse scale. Results of stepwise multiple regression showed that personality traits: extraversion, neuroticism personality, openness to experience, substance abuse and loneliness statistically and significantly predict childhood sexual abuse. Agreeableness (β =.18, p = > 0.01) and conscientiousness (β = .06, p = > 0.01) do not statistical and significantly predictors of childhood sexual abuse. The study concludes that school administrators should always deem it necessary to understand substance abuser and personality traits of an individual that are vulnerable to childhood sexual abuse. The study recommends that government should make some laws and policies through which an immediate actions can be taken against the offenders and abusers childhood sexual abuse.